Genetic engineering of Saccharomyces cerevisiae for efficient polysaccharide utilisation - Gundllapalli, Sarath Babu (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Microbiology))--University of Stellenbosch, 2005.